2002
DOI: 10.1111/j.1530-0277.2002.tb02662.x
|View full text |Cite
|
Sign up to set email alerts
|

Executive Dysfunction and Clinical Outcome in Chronic Alcoholics

Abstract: The BADS total profile score is related to alcohol-nonspecific outcome but not to alcohol-specific outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 32 publications
2
35
1
2
Order By: Relevance
“…Deficits in executive functioning would thus seem to be a significant impediment to positive treatment outcomes. Indeed, executive function has been associated with employment outcomes in patients who were not in treatment (Moriyama et al, 2002). Thus, our findings of executive dysfunction early in abstinence suggest that clinicians might consider tailoring treatment approaches for recently detoxified alcoholics in ways that demand less of these functions-particularly in the domains of learning, reasoning, and cognitive flexibility-as has been suggested for cognitive dysfunction in general (McCrady and Smith, 1986).…”
Section: Self-perception Of Cognitive Deficitsmentioning
confidence: 57%
See 3 more Smart Citations
“…Deficits in executive functioning would thus seem to be a significant impediment to positive treatment outcomes. Indeed, executive function has been associated with employment outcomes in patients who were not in treatment (Moriyama et al, 2002). Thus, our findings of executive dysfunction early in abstinence suggest that clinicians might consider tailoring treatment approaches for recently detoxified alcoholics in ways that demand less of these functions-particularly in the domains of learning, reasoning, and cognitive flexibility-as has been suggested for cognitive dysfunction in general (McCrady and Smith, 1986).…”
Section: Self-perception Of Cognitive Deficitsmentioning
confidence: 57%
“…It is reasonable to infer that these observed cognitive lapses would have affected real-world functioning in persons with chronic alcohol abuse. Cognitive impairment has been related to posttreatment employment success (Donovan et al, 1984;Moriyama et al, 2002); we found a correlation with an indicator of past employment success (on the ASI). Consistency in this finding may reflect the greater cognitive demnds of work environments.…”
Section: Self-perception Of Cognitive Deficitsmentioning
confidence: 60%
See 2 more Smart Citations
“…Examples of tests used to examine executive processes include dual-task performance, Stroop, Wisconsin Card Sorting, Tower of London, delayed alternation, and assorted working memory (WM) tasks. Such paradigms have proved a reliable method for demonstrating executive control deficits across a range of clinical conditions (Dalrymple-Alford et al 1994;Diamond 1996;Baddeley et al 1997;Barkley 1997;Diamond et al 1997;Konrad et al 2000;Baddeley et al 2001;Bennetto et al 2001;Gilotty et al 2002;Sharma and Antonova 2003;Simon et al 2003), with recent work also indicating a strong relationship between executive control deficits on laboratory tasks and real-world behavioral problems (Burgess et al 1998;Kibby et al 1998;Moriyama et al 2002;Kalechstein et al 2003a;Odhuba et al 2005;Chaytor et al 2006). …”
Section: Executive Control Processes and Their Constituent Neural Netmentioning
confidence: 99%